2013
DOI: 10.1371/journal.pone.0070343
|View full text |Cite
|
Sign up to set email alerts
|

MRI Phantoms – Are There Alternatives to Agar?

Abstract: The suitability of different gelling agents as MRI phantoms was evaluated in terms of homogeneity, gel stability and reproducibility. Time and effort for preparation were also taken into account. The relaxation times of various gel compositions were estimated. Carbomer-980 and Carbopol-974P were determined to be promising novel phantom materials. These gelling agents are readily available, inexpensive and easy to handle given that thermal treatment is not required. Furthermore, the viscoelasticity of their pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 23 publications
(30 reference statements)
3
91
0
1
Order By: Relevance
“…It is observed that synthetic polymer-based gels can be a good alternative to agar, because of their long-term stability and easy synthesis (Hellerbach et al, 2013). The main advantage of gel applications in DWI and DTI phantoms (which have fiber bundles and/or other structures where diffusion is anisotropic) is the reduction of flow and convective effects that cause image artifacts (Hellerbach et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is observed that synthetic polymer-based gels can be a good alternative to agar, because of their long-term stability and easy synthesis (Hellerbach et al, 2013). The main advantage of gel applications in DWI and DTI phantoms (which have fiber bundles and/or other structures where diffusion is anisotropic) is the reduction of flow and convective effects that cause image artifacts (Hellerbach et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors say that is impossible to build a multi-purpose MRI phantom (Hellerbach et al, 2013). They are based on the fact that each technique requires specific structures and materials with T1 and T2 compatible to the studied parameter (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations